Discordance between self-reported premarital and post-marital parental sickle cell status - Chizoma I, Eneh (Indian Journal of Child Health, 2020)
Background: Sickle cell disease (SCD) is an autosomal recessive disorder with mutation in the hemoglobin gene. Sickle cell anemia (SCA), the homozygous state, has adverse effects. Community knowledge regarding personal sickle cell status and the inheritance pattern of SCD remain inadequate. Moreover, the influence of wrong laboratory sickle screening result has not been elucidated. Objectives: The objectives of the study were to determine the impact of self-reported parental sickle cell screening, parental understanding of the inheritance pattern of SCA, and prevalence of discordant screen results. Materials and Methods: A cross-sectional clinic-based survey was conducted. Short interviewer-administered questionnaire was used to obtain biodata, history and availability of parental screening and results, understanding of the mode of inheritance of SCA, and decisions about marriage with at-risk partners before marriage. There were 74 parents enrolled by consecutive sampling. Chi-square and Fisher’s exact test were used to analyze inferential variables such as discordant premarital screen result, relationship between premarital screening, and knowledge of mode of inheritance. The prevalence of screening, knowledge of mode of inheritance, and other descriptive data were analyzed with frequency and percentage tables using SPSS version 25. Results: Parents with premarital screen were 39 (52.7%) and 51 (68.9%) had post-marital screen. Discordance was observed between premarital (AS/AA and AA/AA) and post-marital (AS/AS) screen results ([32 (82.1%); 7 (17.9%)] [p<0.001]). A significant relationship existed between knowledge of mode of inheritance and premarital screening in fathers and mothers ([85.0%; 87.5%] [p?0.001; 0.003], respectively) as well as socioeconomic class (p=0.010; 0.019). The difference between unwillingness to marry 57 (81.4%) and willingness to marry 13 (18.6%) was significant (p?0.001). Conclusion: Knowledge of personal sickle cell status seems to be marred by poor access to proper diagnostic tools. This supports the need to enhance policy efforts toward proper diagnosis within the country.